Propionic acid-based additive with surfactant action in reconstituted corn grain silage on nutritive value and performance of ruminants - Silva Neto, Álvaro Bernardo da (2022)
The ensilage of ground corn grain with high moisture content is a technique that, in addition to allowing the storage of the grain, provides a food with better nutritional quality compared to dry corn, due to physicochemical transformations that result in an increase in availability of starch. This increase in starch digestibility occurs due to the proteolysis process of the protein matrix that surrounds the starch granules, mainly triggered by bacterial proteases. The use of additives that help in the proteolysis process is an alternative to obtain a high nutritional quality food with a reduced fermentation time. In a study by Oliveira (2020) with rehydrated corn silage, evidence was found that ensiling with a propionic acid-based additive with surfactant properties can enhance proteolysis in reconstituted corn and its ruminal degradability. To evaluate this hypothesis, two experiments were designed with rehydrated corn ensiled for different times on the performance of two categories of ruminants. The first experiment used 18 Holstein dairy cows, under a 3x3 Latin square design, with three treatments: reconstituted corn ensiled for 30 days (30 CON); ensiled for 60 days (60 CON); and ensiled with additive for 30 days (30 MYC), seeking to evaluate dry matter and nutrient intake, milk yield and composition, ingestive and selective behavior and digestibility of nutrients. The second experiment used 36 Dorper lambs, in a randomized complete block design with two subsequent periods, with three treatments: reconstituted corn ensiled for 50 days (50 CON); ensiled for 90 days (90 CON); and ensiled with additive for 50 days (50 MYC), seeking to evaluate dry matter and nutrient intake, weight gain and selective behavior. In both experiments, the bromatological and fermentative profile of the silages were analyzed, and a ruminal degradability assay was conducted using dairy cows. Experiment 1: the cows were housed in a free stall confinement system, and allocated to individual feed bunks equipped with individual access control and feed monitoring system. The feeding management consisted of two daily offers, and the cows were milked twice a day. The extended conservation time of the 60 CON silage increased the soluble nitrogen content and the ruminal degradability of dry matter in relation to the other silages with 30 days. Although the silage treated with additive had similar soluble protein content compared to 30 CON silage, the ammonia content and its concentration in soluble N were significantly higher for the former. The 30 MYC silage had higher lactic acid content compared to the other silages. There was a significant decrease in the geometric mean particle size and an increase in the surface area and proportion of fine particles in the rehydrated corn silage with the use of the additive. No changes were observed in the dry matter degradability of 30 MYC silage against the control silage, but there was a significant decrease of the ruminal degradation rate (kd) with the use of the additive. There were no significant changes in dry matter intake, milk yield and composition for the cows fed the additive-treated silage. However, the presence of the additive in rehydrated corn silage promoted greater selection against long particles in the diet, and a greater selection in favor of fine particles, reflecting in lower NDF intake by cows when treated with the diet containing 30 MYC silage, but without harming rumination and chewing activity. Experiment 2: the longer conservation time of 90 CON silage and between periods promoted an increase in the soluble protein and ammonia contents and in the ruminal degradability of dry matter. Although no gain in the extent of degradation was observed, the longer ensiling time increased the soluble fraction at the expense of the potentially degradable fraction. Although the 50 MYC silage had similar soluble nitrogen content compared to 50 CON silage, its ammonia content was significantly higher, and its concentration of NH3-N in soluble N was higher than that observed in the other treatments. The 50 MYC silage presented the lowest concentrations of lactic acid between the treatments, however ethanol and butyric acid contents were significantly lower in the additive-treated silage. There were no changes in dry matter degradability after 12 h of ruminal incubation and in degradation rate (kd) of the 50 MYC silage against the 50 CON silage, but the additive promoted a higher indigestible fraction of corn compared to the other treatments, and there was a reduction in the ruminal soluble fraction only in the second period in relation to the 50 CON silage. The effective degradability only tended to be lower for the additive-treated silage when passage rates (kp) were assumed at 5 and 8%/h, but for 2%/h it was significantly lower in relation to the 50 CON silage. There was no effect of ensilage time or additive on dry matter intake, weight gain and feed efficiency of the lambs. The silage treated with the additive did not change the selective behavior of the lambs.